The evaluation between vitamin D level and pelvic organ prolapse in post-menopausal women - Rani Paul, Zhuma; Khanam, Nurun Nahar; Chandra Barai, Shyamal; Parvin, Mst. Nargis; Talukder, Plabony; Siddiqua, Masrura; Nahar, Nurun; Sultana, Nigar; Rahman, Nasima; Haque Dona, Georgia; Jahan, Samanta; Koly, Homyera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Vitamin D is important for skeletal integrity and optimal muscle function. The high incidence and prevalence of vitamin D deficiency and pelvic organ prolapse have been found in postmenopausal women, raising the question of whether the entities are related. The aim of the study was to evaluation between vitamin D level and pelvic organ prolapse in post-menopausal women. Methods: This case control study has been designed and conducted in the Department of Obstetrics and Gynecology, BSMMU to investigate the level of vitamin D in patients with and without pelvic organ prolapse to explore the association of vitamin D with pelvic organ prolapse. After taking informed written consent the serum vitamin D level of all participants was measured by CMIA technology with flexible assay protocols at Biochemistry and Molecular Biology department of the same institute. Statistical analysis of the results was obtained by using window-based computer software devised with Statistical Packages for Social Sciences (SPSS-24). Results: The study population was divided into two groups, a case group (n=74) consisting of patients with pelvic organ prolapse and a control group (n=74) comprising of women without pelvic organ prolapse. A total 148 participants of 52 years or older attending the out or inpatient department were enrolled in the study. Mean±SD level of Vitamin D in the case group was 13.96±5.18 ng/ml and in the control, group was 21.08±5.77 ng/ml respectively. The difference was statistically significant (p<0.05). Moreover, the vitamin D levels were inversely proportionate with the severity of pelvic organ prolapse. Conclusions: Vitamin D deficiency may be an important systemic factor associated with pelvic organ prolapse. Measuring vitamin D levels in postmenopausal women and replenishing deficiencies may also be important for the pelvic floor.